"I Guess that the Greatest Freedom … ": A Phenomenology of Spaces and Severe Multiple Disabilities. Issue 2 (4th May 2017) - Evensen, Kristin Vindhol; Standal, Øyvind Førland
Abstract: This paper expresses wonder about how bodies in motion can lead towards an understanding of lived meaning in silent lifeworlds. In such lifeworlds, expressions are without words, pre-symbolic, and thus embodied. To address the wonder, phenomenological philosophy and phenomenological methodology were employed to frame an approach that acknowledges lives with disabilities as qualitatively different from, and yet not inferior to, nor less imbued with meaning than, lives without. The paper focuses on spatiality as decisive in determining possibilities for persons to express their perspectives through a wide range of movements. Movements take place in the continuum between the spatiality of positions as objective bodily sensations and the spatiality of situations as embodied interactions with others and the world. Thus, in order to access the perspectives of students with severe and multiple disabilities, transitions between and movements within different spaces are examined. Approaching an educational everyday life where students are restricted in the possibilities available to them for moving in and out of spaces, the study reported points to the importance of recognizing the relationship between subjective movements and the spaces enveloping them as what creates a spatiality that is meaningful to the subject. It is accordingly suggested that choosing which spaces to include in educational contexts are formative choices that express a view of humanity. The paper also emphasizes the importance of recognizing temporality as a pedagogical resource when detecting and acting upon students' changing expressions.